Department of Historic Objects Conservation, Faculty of Building and Architecture, Lublin University of Technology - Trochonowicz, Maciej (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
State of knowledge about how to use chemical injection in calcareous rock is unsatisfactory. This results, primarily, from the locality using of the stone and its small porous structure. Companies offering preparations to carry out this type of insulation, usually focus on the walls made of widely used in construction materials. Offered measures have not been tested for their applicability in such an unusual and as it turns out, the „difficult” material. The first of two articles will be devoted to research the possibility of producing a hydrophobic layer in calcareous stone and mortar and an assessment of its effectiveness.